THE FÖRSTER-TYPE EXCITON QUENCHING MECHANISM AND ITS IMPACT TO THE QUANTUM EFFICIENCY AND EXCITON DIFFUSION IN ORGANIC SEMICONDUCTOR - Divayana, Yoga (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
Organic light-emitting diodes (OLEDs) have emerged as one of the most important generallighting technologies of the future. The current state-of-the-art OLED utilizes various differentlayers which function separately as carriers transport, carriers and excitons blocker, and emittinglayer. The emission layer of the OLED is normally formed by a host-guest system obtained byco-evaporating a small amount of guest molecule in the matrix of host material. It is generallyaccepted that in a host-guest system, concentration quenching is caused by molecules aggregation.As concentration of guest molecule increases, a drop in quantum efficiency is followed by a redshiftin the emission spectrum, characteristics of aggregate state. Here we show that concentrationquenching is also caused by another Förster-type interaction. We investigate this Förster-typeexciton quenching process in various organic molecules and its effect to the exciton diffusion.